Understanding the Challenges and Strategies of Elementary Teachers in Teaching Numeracy Skills - Clarion, Jennifer D. (International Journal of Research in Interdisciplinary Studies, 2024)
This phenomenological study excavated the challenges and strategies of teachers in teaching numeracy particularly in New Corella District, Division of Davao del Norte. This also probed their coping mechanisms from the challenges they encountered, and their insights drawn from the findings of this study. Qualitative – phenomenological study was employed in exploring the views of the ten (10) elementary teachers of which primary instrument of data gathering was through in- depth interview. Major findings revealed that educators face various challenges in this endeavor, and three prominent issues are the low critical thinking skills of students, limited student engagement, and a lack of access to information and communication technology (ICT). Furthermore, three key strategies employed by teachers to enhance problem-solving skills are problem-based learning (PBL), the scaffolding approach, and fostering metacognition and self-regulation. Finally, the landscape of teaching problem-solving skills in mathematics is continually evolving, and educators play a pivotal role in shaping effective instructional practices. Three major themes emerge from the insights of teachers that are crucial to educational management: adaptive pedagogy, technology integration and access, and professional collaboration and learning communities. The exploration of challenges and strategies faced by teachers in teaching numeracy in mathematics for learners holds significant implications for educational research. Understanding the intricacies of this pedagogical landscape provides valuable insights that extend beyond the immediate classroom setting. These research findings have broad implications for teacher professional development, curriculum design, and educational policy formulation. By uncovering the challenges teachers encounter, researchers can inform targeted interventions and support systems to enhance teacher efficacy.